An adaptable vacuum gripper design for egg packaging, attached to the KUKA KR 60-3 industrial robot (LACCEI, 2024)
Packaging is one of the main processes for a company to satisfy the requirements imposed by the consumer within the production chain however, at present, the automation of this process has not been fully developed in the poultry industry in Peru, delegating the responsibility to a significant number of workers. Due to this, there are long working hours, production delays, the integrity of both personnel and the product is exposed, and the trust placed by the consumer is compromised. In consideration of the technological advances involved in industry 4.0 and the complexity of developing an end effector capable of adapting to multiple variations in the egg packaging process, an Adaptable Vacuum Gripper design is proposed, coupled to the KUKA KR 60 industrial Robot. -3, that it be dynamic and efficient when packing a maximum of 30 eggs in their respective cardboard or plastic commercial packaging without compromising the state of the product, alternating the number of eggs packed in relation to the distribution matrix of the end effector ( 5×6) and the capacity established by the type of packaging to be packaged. Likewise, the product can be coupled to any type of industrial robot through insignificant modifications that alter its base structure. With the proposed mechatronic device, it was possible to obtain an efficiency of 100%.